(untitled) (Swiss Medical Weekly, 2013)
The 2010 American Heart Association guidelines now recommend leadership training in Advanced Cardiac Life Support courses. In this review we provide a comprehensive summary of data derived from clinical studies that investigated the importance of leadership in cardiopulmonary resuscitation (CPR). Only a few, mostly observational, studies have been conducted under real-life conditions because of the high heterogeneity of the situations, difficulties in capturing the initial phase of CPR, and ethical issues. Well-controlled studies in the human simulator can fill existing gaps and provide important insights. High-fidelity video-assisted simulator studies from different research groups have shown that a prolonged process of teambuilding is associated with significant shortcomings in CPR, whereas effective leadership improves team performance. In addition, randomised controlled studies have provided evidence that medical students receiving leadership training subsequently showed improved CPR performance, which was sustained after a follow up of 4 months. In addition, leadership is influenced by gender and other factors such as emotional stress. Future studies are needed to investigate cultural differences and how findings from the simulator can be transferred to real-life situations.